2014
DOI: 10.1093/eurheartj/ehu094
|View full text |Cite
|
Sign up to set email alerts
|

Evolving concepts of angiogram: fractional flow reserve discordances in 4000 coronary stenoses

Abstract: The data confirm that one-third of a large patient population shows discordance between angiogram ≥ 50%DS and FFR ≤ 0.8 thresholds of stenosis severity. Left main stenoses are often underestimated by the classical 50% DS cut-off compared with FFR. This discordance offers physiologic insights for future trials. It is hypothesized that the discordance between angiography and FFR is related to technical limitations, such as imprecise luminal border detection by angiography, as well as to physiologic factors, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(145 citation statements)
references
References 44 publications
8
134
0
3
Order By: Relevance
“…[179][180][181] Quantitative noninvasive and invasive techniques are now available that go beyond standard interpretation of anatomic coronary stenosis in making this functional assessment. These include noninvasive assessment of maximum MBF and MFR with PET, as well as invasive measurement of CFR and FFR.…”
Section: Physiologic Relationships Among Mfr Ffr and Relative Flow mentioning
confidence: 99%
“…[179][180][181] Quantitative noninvasive and invasive techniques are now available that go beyond standard interpretation of anatomic coronary stenosis in making this functional assessment. These include noninvasive assessment of maximum MBF and MFR with PET, as well as invasive measurement of CFR and FFR.…”
Section: Physiologic Relationships Among Mfr Ffr and Relative Flow mentioning
confidence: 99%
“…33 In the present analysis, we compared side-by-side VE and QCA to FFR and studied the effect of risk factors on these relationships.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between angiographic stenosis severity and functional significance assessed by FFR and the mismatch between these 2 measures have been extensively investigated to optimize percutaneous coronary intervention (PCI) 16, 24, 25, 26. Clinical factors, including age, sex, angiographical lesion‐related factors, and physiological factors, have been reported to contribute to visual‐functional mismatch and reverse mismatch 15, 16, 26, 27, 28. Our results were in line with these previous studies and further suggested the importance of microvascular function in both mismatch and reverse mismatch.…”
Section: Discussionmentioning
confidence: 99%